# Solve for y 2y-2+5(2y+2)=-2(y+1) 2y-2+5(2y+2)=-2(y+1)
Simplify 2y-2+5(2y+2).
Simplify each term.
Apply the distributive property.
2y-2+5(2y)+5⋅2=-2(y+1)
Multiply 2 by 5.
2y-2+10y+5⋅2=-2(y+1)
Multiply 5 by 2.
2y-2+10y+10=-2(y+1)
2y-2+10y+10=-2(y+1)
12y-2+10=-2(y+1)
12y+8=-2(y+1)
12y+8=-2(y+1)
12y+8=-2(y+1)
Simplify -2(y+1).
Apply the distributive property.
12y+8=-2y-2⋅1
Multiply -2 by 1.
12y+8=-2y-2
12y+8=-2y-2
Move all terms containing y to the left side of the equation.
Add 2y to both sides of the equation.
12y+8+2y=-2
14y+8=-2
14y+8=-2
Move all terms not containing y to the right side of the equation.
Subtract 8 from both sides of the equation.
14y=-2-8
Subtract 8 from -2.
14y=-10
14y=-10
Divide each term by 14 and simplify.
Divide each term in 14y=-10 by 14.
14y14=-1014
Cancel the common factor of 14.
Cancel the common factor.
14y14=-1014
Divide y by 1.
y=-1014
y=-1014
Simplify -1014.
Cancel the common factor of -10 and 14.
Factor 2 out of -10.
y=2(-5)14
Cancel the common factors.
Factor 2 out of 14.
y=2⋅-52⋅7
Cancel the common factor.
y=2⋅-52⋅7
Rewrite the expression.
y=-57
y=-57
y=-57
Move the negative in front of the fraction.
y=-57
y=-57
y=-57
The result can be shown in multiple forms.
Exact Form:
y=-57
Decimal Form:
y=-0.714285‾
Solve for y 2y-2+5(2y+2)=-2(y+1)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top